Molecular dynamics simulations of displacement cascades in vanadium: Generation and types of dislocation loops - Rongyang Qiu; Yangchun Chen; Ning Gao; Xinfu He; Yankun Dou; Wen Yang; Wangyu Hu; Huiqiu Deng (Nuclear Materials and Energy, 2023)
Vanadium(V)-based alloys have received extensive attention as promising first-wall and blanket candidates for fusion reactors. In the present study, molecular dynamics (MD) simulations have been performed to study the displacement cascades in V bulk with the recoil energy up to 80 keV at 300 K. The results indicate that the clustering fraction and cluster size of vacancies are higher than those of interstitials. The nucleation, evolution, and energy of dislocation loops are studied. It’s found that 1/2 〈111〉 interstitial and vacancy dislocation loops are the primary ones, while low concentration 〈100〉 vacancy loops are also formed. In addition, the nucleation of 1/2 〈111〉 interstitial dislocation loops is earlier than that of 1/2 〈111〉 vacancy ones. The reason for the appearance of 1/2 〈111〉 vacancy dislocation loops is that the formation energy of the 1/2 〈111〉 vacancy dislocation loops is close to that of voids containing the same number of vacancies. These results provide a new understanding of applying V-based alloys in fusion reactors.